Robotic Staging of Cervical Cancer With Simultaneous Detection of Primary Pelvic and Secondary Para-Aortic Sentinel Lymph Nodes: Reproducibility in a First Case Series - Van Trappen, Philippe; De Cuypere, Eveline; Claes, Nele; Roels, Sarah (Frontiers in Surgery, 2022)
Objective Discrepancies exist among international guidelines on the surgical staging of para-aortic lymph nodes in locally advanced cervical cancer (LACC), varying from considering a para-aortic lymph node dissection, at least up to the inferior mesenteric artery, to a complete para-aortic lymph node dissection. In this study, we aim to assess the reproducibility of our recently reported robotic technique using indocyanine green for identifying besides primary pelvic sentinel lymph nodes (SLNs), secondary para-aortic SLNs in a first case-cohort of cervical cancer patients. Methods A retrospective case series of LACC patients with/without suspicious pelvic lymph nodes (LNs) on imaging (including two patients with an additional suspicious para-aortic LN) is reported. All patients underwent a robotic pelvic SLN and para-aortic sentinel/nonsentinel LN dissection using the da Vinci Xi platform. Indocyanine green was used as a fluorescent tracer, at a concentration of 1.9 mg/mL, and injected as 0.5 mL in each quadrant of the cervix. Results In a total of 10 cases, primary pelvic SLNs (90% bilateral) with subsequent secondary para-aortic SLNs were identified in all cases. Lower para-aortic SLNs were present in all cases, and upper para-aortic SLNs were found in 9 out of 10 cases. The mean age of the cervical cancer patients was 49.8 years (SD ± 6.89), and the mean body mass index (BMI; kg/m2) was 23.96 (SD ± 4.60). The median total operative time was 105.5 min (range: 89–141 min). The mean numbers of primary pelvic SLNs and secondary lower and upper para-aortic SLNs were 3.10 (SD ± 1.10), 2.90 (SD ± 0.74), and 2.30 (SD ± 1.57), respectively. The median number of total para-aortic LNs (PALNs) dissected per patient was 11.5. Six patients had positive primary pelvic SLNs, and two had secondary positive para-aortic SLNs. The nonsentinel para-aortic LNs were negative in all cases. There were no intra- or postoperative complications. Conclusion Our preliminary experience demonstrates the reproducibility of identifying, besides primary pelvic SLNs, secondary lower and upper para-aortic SLNs during robotic staging in LACC. A surgical approach limiting a complete para-aortic LN dissection could reduce the potential risks and morbidity associated with this procedure. To determine the sensitivity and negative predictive value of this new surgical approach, and whether the lower para-aortic SLNs under the inferior mesenteric artery are representative of the whole para-aortic region, large prospective observational studies are needed in LACC and/or those with suspicious pelvic LNs but apparent normal para-aortic LNs on imaging.